Analisis Kesalahan dalam Menyelesaikan Soal Cerita Persamaan Garis Lurus ditinjau dari Gaya Berpikir Siswa Kelas VIII SMPN 5 Mataram Tahun Pelajaran 2021/2022 - Munawarah Munawarah; Laila Hayati; Eka Kurniawan; Baidowi Baidowi (Griya Journal of Mathematics Education and Application, 2023)
The aims of this study were: 1) to describe the mistakes made by students in solving linear equations based on Watson's criteria in terms of students' thinking styles and 2) the factors that caused students to make these mistakes. This research is a qualitative descriptive study involving 29 students of class VIII D SMPN 5 Mataram as research subjects. Data on types of errors and factors that caused students to make mistakes in solving linear equation word problems were obtained through tests in the form of word problems and interview guides. The results showed that students with each type of concrete sequential, abstract sequential, concrete random, and abstract random thinking styles made mistakes that varied from the eight types of errors in Watson's criteria. Students with concrete random thinking styles make the most diverse mistakes compared to other types of thinking styles. Some of the factors that cause students to make mistakes in solving linear equation word problems are using the wrong formula, not mastering the concept of determining gradients and linear equations, lack of practice questions, not being thorough, having weak mastery of algebraic operations, unable to understand questions, ability to write mathematics low, and lack of mastery of the prerequisite material, namely point coordinate material.